Occasional Collocations in P. B. Shelley’s Poem “Ginevra” - M. V. Vlavatskaya; A. V. Emelyanova (Научный диалог, 2019)
The article is devoted to functional-semantic analysis of occasional collocations in P. B. Shelley’s poem “Ginevra.” The study is carried out in the framework of combinatorial linguistics, which studies the combinatorial and syntagmatic properties of language units. The relevance of the work is associated with the study of atypical, non-usual phrases, which have a rich semantic potential, so that they are a valuable linguistic tool in the creation of artistic and poetic works. The lexical meaning of such units is not fixed in dictionaries and can be defined only within a certain context. The purpose of this article is to reveal the semantics and functions of occasional collocations in P. B. Shelley’s poem “Ginevra” by means of functional-semantic analysis. Occasional collocations are defined as non-normative combinatorially conditioned, individual-author combinations of words formed on the basis of intentional violation of lexico-semantic compatibility, created by the author once to perform functional and expressive tasks within a particular work. To achieve this goal, it is necessary to study the concept of “occasional collocation,” to identify ways of formation of occasional units and their functional purpose through a comprehensive method of research - functional-semantic analysis.